Generating orbital angular momentum based on circular antenna array with filtering characteristic. Issue 8 (23rd April 2021) - Lei, Ruiting; Li, Sirong; Yang, Yang; Liu, Baiyang; Zhang, Li
Abstract: The circular antenna array with filtering characteristic for orbital angular momentum's (OAM) generation is proposed in the paper. An antenna unit consisting of one patch with V‐shape slots, two shorting pins and defected ground structures is firstly designed, simulated, and measured. And the simulated and experimental results demonstrate that the designed antenna has a great filtering respond with a flat gain about 5 dB from 5.1 to 5.5 GHz. The filtering units are then used to form an eight‐unit circular filtering array to generate vortex waves carrying OAM modes of l  = ±1. Simulated results show that the proposed filtering array can generate vortex waves with high purity of more than 89%. Moreover, using two antenna arrays, the wireless communication is also simulated and the isolation between two OAM modes is larger than 14 dB, which further verifies the orthogonality between the generated two OAM modes. Our proposed antenna array with filtering characteristic can not only enhance the channel capacity but may also help to avoid abnormal frequency interference, which shows great potentiality in wireless communication.